Drought Assessment - Nagarajan, R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Information-based decision-making during drought, often brings out some of the excellent practices that are prevalent in society / individuals. This book is designed to provide information on the drought process, meteorological, hydrological, agriculture, socio-economic aspects and available technologies such as satellite remote sensing data analysis and Geographical Information system for assessment. Assessment procedures utilising the various parameters of importance from various sources for micro level management that would enhance the effectiveness of management practice are dealt in detail. Resource availability and affected group determine the relief assistance for the present event and information that would help them in their realisation and preparedness for the forthcoming years by select countries is highlighted. This would help in the formulation of schemes for event mitigation and area development plans. The readers would gain complete knowledge on drought. This book is expected to act as a guide in preparing people as effective natural resource utilizationist under drought situations.
Meteorology -- Water Resources -- Agriculture -- Drought Indices -- Satellite Remote Sensing -- Spatial Data and Geographical Information System -- Vulnerability Assessment -- Resources, Drought Events and Management Profile of Countries.
Keywords: Earth sciences; Meteorology; Natural disasters; Remote sensing; Agriculture; Environmental management; Water pollution; Earth Sciences; Natural Hazards; Environmental Management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Agriculture; Meteorology; Remote Sensing/Photogrammetry.; Electronic books